Regional design in the context of fragmented territorial governance: South Wing Studio - Balz, Verena; Zonneveld, Wil (A+BE | Architecture and the Built Environment, 2019)
In the Netherlands, the formation of governance arrangements around planning issues that cross administrative boundaries has been assisted frequently by a design approach that is often referred to as “regional design”. This is a distinctive method of policy argumentation that makes use of spatial representations of the plausible future of regions. Such representations are intended not only to indicate physical changes, but also to stimulate debate on sharing responsibilities and resources for planning tasks among planning actors. This paper contributes to a better understanding of the performance of regional design in the context of fragmented regional governance through a case study in the southern part of the Randstad in the Netherlands. We argue that regional design has contributed to institutional capacity in a complex polycentric and, looking at the governance structure, pluricentric region like the Randstad South Wing, largely by allowing for multiple interpretations.